SOCIO-JURIDIC ANALYSIS OF ABORTION ACCORDING TO ARTICLE 75 OF LAW NO. 36/2009 CONCERNING ON HEALTH AND LAW NO. 35/2014 CONCERNING ON CHILD PROTECTION - Triwulandari, Endah; Tarsono, Edy (jfpublisher, 2022)
Children are often become victims of sexual crimes that cause the pregnancy. Not infrequently abortion is chosen as a way in overcoming Unwanted Pregnancy (KTD). The Criminal Code prohibits abortion. In Law No. 36/2009 concerning Health in Article 75 allows for abortion but Article 76 indicates that when the abortion is not in accordance with the requirements in Article 76, then a child who is a rape victim who has an abortion can be subject to a criminal offense under Article 194 of the Health Law. The type of this research is normative legal research. Normative legal research is research that focuses on positive legal norms. Abortion in certain cases can be justified when it is an abortion that is medically recommended by the treating doctor, for example because the pregnant woman suffers from an illness and to save the woman's life, the pregnancy must be aborted.